Woodlands and welfare in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The miombo in transition: woodlands and welfare in Africa edited by Bruce Campbell 1966 266pp ISBN 979 8764 07 2